The effect of roselle flower petals extract (Hibiscus sabdariffa Linn.) on reducing inflammation in dextran sodium sulfateinduced colitis - Masrul Lubis; Gontar Alamsyah Siregar; Hakim Bangun; Syafruddin Ilyas (Medicinski glasnik, 2020)
Aim: To determine the effect of roselle (Hibiscus sabdariffa) petals in dextran sodium sulfate (DSS)-induced colitis model by measuring pro-inflammatory cytokines expressions (IL-6, and TNF-?), anti-inflammatory cytokine expression (IL-10) and histological colitis inflammation score (HCIS). Methods: This study was conducted in two phases. For the first phase, five DSS-induced colitis mice were sacrificed (group 1) and compared with six healthy mice (group 2) after five-cycle induction (70 days). For the second phase, roselle-treated DSS-induced colitis mice were sacrificed on day 7, 14, 21, and 28 after induction and compared with mesalazine-treated DSS-induced colitis mice. Expressions of IL-6, TNF-?, and IL-10 were determined by immunohistochemistry and HCIS were assessed by two experienced pathologists. Results: The expressions of IL-6, TNF-?, and IL-10, and HCIS in DSS-induced colitis mice were increased compared with control. The expressions of IL-6, TNF-? were significantly higher in roselle-treated group on day 7 and 14, but not on day 21 and 28, whereas, the expression of IL-10 was significantly lower only on day 7 compared with mesalazine-treated group. The inflammation was higher in roselle-treated group assessed by using HCIS. Compared to day 0, the reduction of HCIS was significant in roselle-treated and mesalazine-treated groups. Conclusion: Roselle flower petal can attenuate the inflammation in DSS-induced colitis in mice. The extract of roselle can be given as an adjuvant therapy to the first-line therapy to enhance anti-inflammatory effect by increasing expression of anti-inflammatory cytokines and decreasing pro-inflammatory cytokines.
Keywords: anti-inflammatory; cytokines; immunohistochemistry; inflammatory bowel disease; plant extract